Misconceptions of the p-value among Chilean and Italian Academic Psychologists - Badenes-Ribera, Laura; Frias-Navarro, Dolores; Iotti, Bryan; Bonilla-Campos, Amparo; Longobardi, Claudio (Frontiers in Psychology, 2016)
The p value misconceptions are based on certain beliefs and attributions about the significance of the results. Thus, they affect the professionals’ decisions and jeopardize the quality of interventions and the accumulation of valid scientific knowledge. We conducted a survey on 164 academic psychologists (134 Italians, 30 Chileans), questioned on this topic. Our findings are consistent with original research and suggest that some participants do not know how to correctly interpret p values. The inverse probability fallacy presents the greatest comprehension problems, followed by the replication fallacy. These results highlight the importance of the statistical re-education of researchers. Recommendations for improving statistical cognition are proposed.